Prevalence and Risk Factors of Burnout Among Female Oncologists From the Middle East and North Africa - Abusanad, Atlal; Bensalem, Assia; Shash, Emad; Mula-Hussain, Layth; Benbrahim, Zineb; Khatib, Sami; Abdelhafiz, Nafisa; Ansari, Jawaher; Jradi, Hoda; Alkattan, Khaled; Jazieh, Abdul Rahman (Frontiers in Psychology, 2022)
Background: Burnout (BO) is a recognized challenge among the oncology workforce. It affects both genders with a higher frequency among women. This study examined the factors contributing to the development of burnout among female oncologists from the Middle East and North Africa (MENA). Methods: An online cross-sectional survey was distributed to oncology professionals from different countries in the MENA region. The validated Maslach Burnout Inventory (MBI) of emotional exhaustion (EE), Depersonalization (DE), and Personal Achievement (PA) plus questions about demography/work-related factors and attitudes toward oncology were included. Data were analyzed to measure BO prevalence and related factors. Results: Between February 10 and March 15, 2020, 545 responses were submitted by female oncologists. The responses pre-dated the COVID-19 pandemic emergence in the region. BO prevalence was 71% among female professionals. Women aged < 44 years represented 85% of the cohort. Sixty-two percent were married, 52% with children and one-third practiced a hobby. Two-thirds worked in medical oncology, worked for < 10 years and 35% worked in academia. The majority (73%) spent > 25% on administrative work daily. Nearly half of the respondents (49%) expressed a recurring thought of quitting oncology and 70% had no burnout support or education. Inability to deliver optimal care was reported as distressing for career development in 82%. Factors significantly influencing the BO risk were identified. Marital status, having children, academia and years in practice did not impact the risk of BO among female oncologists from MENA. Conclusions: Female oncologists from the Middle East and North Africa (MENA) were found to have a high prevalence of BO. In this cohort, the majority of women oncology workers were young and in their early to mid-career stages. Burnout was linked to being younger, practicing in North African nations, having a heavy administrative load, and having persistent thoughts of quitting. Practicing a hobby and engaging in oncology communication, on the other hand, reduced the chance of BO. Burnout support and education, specifically for oncology women, is required.